Afterslip following the 2007 Mw 8.4 Bengkulu earthquake in Sumatra loaded the 2010 Mw 7.8 Mentawai tsunami earthquake rupture zone - Tsang, Louisa Lok Hang (2018)
The 12 September 2007 Mw 8.4 Bengkulu earthquake in Sumatra marked the first in a modern series of large earthquakes along the Mentawai section of the Sunda megathrust. Understanding the spatial distribution of coseismic slip and ensuing afterslip is important for assessing seismic hazard in neighboring unruptured regions of the megathrust. We reestimate the spatial distribution of coseismic slip during this earthquake with improved coseismic offsets from the Sumatran GPS Array (SuGAr) and estimate afterslip following this earthquake with SuGAr postseismic time series spanning ∼6.3 years after the earthquake. We invert for the spatiotemporal distribution of afterslip with the principal component analysis‐based inversion method (PCAIM), and we take into account viscoelastic deformation by incorporating into the inversion the estimation of strain within ductile deforming blocks located at asthenospheric depths. Our results suggest cumulative afterslip concentrated within, updip, and downdip of the 2007 coseismic rupture area and shallow afterslip that borders and overlaps the 2010 Mw 7.8 Mentawai earthquake rupture zone. The cumulative contribution of stress changes due to the coseismic event and the ensuing afterslip likely increased strain rates in the shallow portion of the megathrust adjacent to the Mentawai earthquake rupture area, potentially promoting its rupture in 2010.